Influence of the anion on diffusivity and mobility of ionic liquids composite polybenzimidazol membranes. (10th September 2020) - Compañ, Vicente; Escorihuela, Jorge; Olvera, Jessica; García-Bernabé, Abel; Andrio, Andreu
Abstract: The study of proton conductivity processes has received increasing attention in the past decades due to their potential applications in fields such as electrochemical devices and fuel cells. Despite the high number of composite membranes which have been described for this purpose, fundamental studies of the conduction phenomena in polymeric membranes are scarce. In this article, we study on the effect of the anion on ionic conductivity of ionic liquid composite polybenzimidazole (PBI) membranes. These membranes, which contain 1-butyl-3-methylimidazolium (BMIM) with different counterions ([Cl] –, [NCS] –, [NTf2 ] – and [BF4 ] – ) were analyzed by electrochemical impedance spectroscopy (EIS) in order to study the influence of the anion on the ionic conductivity, but also mobility and charge carrier density at different temperatures. The methodology for this analysis is based on the Coelho model of electrode polarization (EP), where the dependence of the complex dielectric permittivity on frequency is represented in terms of a Cole-Cole function, contrarily to the generally used simple Debye relaxation. The calculated activation energies associated to the conductivity showed a dependence on the anion and is around 65–84 kJ mol −1, which suggests that the ionic conductivity mainly occurs through the vehicle-type mechanism. The calculated diffusivity values followed the trend D NTf2 > D Cl > D BF4 > D SCN, with an associated activation energy (in kJ·mol −1 ) following the trend Eact(NTf2) = 10.9 < Eact(Cl) = 12.6 < Eact(BF4) = 18.5 < Eact(SCN) = 25.1. The comparison between these values reveals that a decrease in the ion binding energies (Eb ) and stabilization energies (Es ) could be responsible for the growth of the diffusion coefficient around one or two orders of magnitude depending on temperature and anion. The low stabilization energy observed for the NTF2 - and Cl − anions in comparison with NCS − and BF4, can be attributed to the poor stabilization of separated ion pairs by coordination with the PBI segments, which is reflected in the values of the dielectric permittivity (εs ) calculated by EIS.